What is the acceptance of video consultations among orthopedic and trauma outpatients? A multi-center survey in 780 outpatients. Issue 11 (November 2021) - Scherer, Julian; Osterhoff, Georg; Kaufmann, Ernest; Estel, Katharina; Neuhaus, Valentin; Willy, Christian; Hepp, Pierre; Pape, Hans-Christoph; Back, David A.
Highlights: The majority of participants would be willing to conduct an online consultation and do own suitable devices. Participants older than 55 years of age are 5-times less likely to conduct an online consultation. Participants would use an online consultation most likely in order to discuss medical findings and for prescriptions rather than for initial presentation of traumatic problems and initial diagnostics. According to this study, advantages of the online consultation are reduction of physical appointments and reduction of travelling. Disadvantages were no physical examination and no incidental findings. Abstract: Introduction: The purpose of the present study was to assess orthopedic and orthopedic trauma patients' willingness to perform hypothetical remote video consultations, possible advantages as well as concerns. Methods: Between June 2019 and November 2019, a survey amongst consecutive regular orthopedic and orthopedic trauma patients at the outpatient clinics from three European level I trauma centers was conducted via paper-based questionnaires, composed of participants` demographics as well as five open and closed questions. Participation was voluntary and anonymity was granted. Results: In total, 780 participants (female 302, 38.7%, male 478, 61.3%) with a mean age of 43.8 years (SD 17.1, range from 14 years to 94 years) were included. The majority of the participants (57, 6%) were eager to use a remote consultation. Participants with an age of more than 55 years were significantly less likely to use a remote consultation than their younger counterparts (OR= 0.18, p=0.003. r 2 =0.141). Among the whole study population, 86.2% stated, that they had a device compatible with an online video consultation. The highest willingness to conduct a video consultation in respect of the participants` occupation was observed in "part-time"-jobs (70.6%), whereas the lowest disposition was seen in retired patients (37.1%) (p= 0.0001). The most stated reason why to conduct a video consultation was "communication of medical findings" (67.8%). The most stated advantage was the "reduction of physical consultations" (66.4%). "No physical examination" was the most frequently stated disadvantage (75.9%). Conclusion: The majority of orthopedic and orthopedic trauma outpatients would use a video consultation, especially because of commuting and time issues and ideally to communicate medical findings, such as x-ray reports or lab values. Elderly patients appear to be less eager in regard to video consultations. These results may change for even better acceptance in view of a current pandemic situation, as experienced since early 2020. We feel that this assumption may warrant further investigation.